Preparation and preliminary evaluation of a soothing gel containing Aloe vera and Perilla frutescens essential oil - Linh Tran Vu Phuong*, Nga Nguyen Linh, Linh Phung Phuong; Inh Cam Thi (Vietnam Journal of Science, Technology and Engineering, 2026)
This article presents the process of developing an innovative skincare product derived from natural ingredients, specifically Aloe vera and perilla leaf essential oil (Perilla frutescens). The product is formulated in a gel-based form, making it lightweight, non-greasy, and suitable for a wide range of skin types, including normal, oily, combination, and especially sensitive skin. By combining clean, affordable, and easily accessible ingredients, the research has successfully created a high-quality skincare solution with excellent moisturising, protective, and regenerative properties at a relatively low production cost. The gel is rapidly absorbed into the skin, providing immediate hydration while delivering essential nutrients that help maintain healthy and balanced skin. Aloe vera extract is well known for its soothing, anti-inflammatory, and healing effects, whereas perilla leaf essential oil contributes antioxidant and skin-brightening benefits. Together, these ingredients help reduce irritation, improve skin texture, and support natural skin recovery. In addition, the product incorporates nanoparticles such as gold (Au) and titanium (Ti), which enhance skin regeneration, reduce dark spots, stimulate collagen production, and promote brighter, smoother, and healthier-looking skin with long-term use.